Investigation of Mechanical Properties of Sansevieria cylindrica Fiber/Polyester Composites - Balasubramani Subramaniam; Manickavasagam V. M; Paul Theophilus Rajakumar I; P.Anantha Christu Raj; Bharath V G; J. Madhusudhanan; Amit Kumar Sharma; Pravin Patil; Gizachew Balcha Assefa (Advances in Materials Science and Engineering)
Natural fiber-reinforced composites are the most cost-effective and environmentally friendly alternative to industrial applications. Composite materials reinforced with Sansevieria cylindrica (SC) fibers were developed in this research work. These fibers were chosen for their outstanding mechanical qualities. Compression moulding was used to create composite materials. Each leaf on a Sansevieria cylindrica plant is 20 to 30 mm thick, with a height of 1000 to 2000 mm. The Sansevieria cylindrica (SC) fibers were used as chemically treated fibers and untreated fibers to produce the composites. The tensile strength, hardness, and impact strength of various fiber weight% of composites (20%, 30%, 40%, and 50%) were calculated. From the tested results, the maximum tensile strength achieved in 40 wt% of treated SC fiber composites is 85.7 MPa. The maximum hardness is found in 40 wt% of composites in both treated and untreated fiber composites. The 40 wt% of composites gives a better impact energy of 9.4 J/cm2.The SC fiber polyester composites have superior interfacial bonding and give maximal strength in treated SC fiber composites. The fiber treatment delivers greater strength than the untreated fiber, according to this study. The treated SC fibers have better strength and good bonding between the fiber and matrix to produce the composite materials.